Perhitungan Volumetrik Cadangan Hidrokarbon pada Reservoir Pasir Padat Berdasarkan Integrasi Inversi Seismik Pre-Stack dan Pemodelan Statik 3D: Studi Kasus Lapangan Penobscot, Cekungan Nova Scotia, Kanada. - Hilal Ramadhan Fikri; Handoyo; Mokhammad Puput Erlangga (Engineering Faculty Universitas Lampung, 2026)
This study investigates the volumetric calculation of hydrocarbon reserves in tight sandstone reservoirs by integrating pre-stack seismic inversion and static modeling. The research focuses on the Penobscot Field in the Scotian Basin, Nova Scotia, Canada, specifically the Middle Mississauga Formation, which contains tight sandstone. The study aims to estimate hydrocarbon reserves in tight sandstone, which has distinct characteristics compared to typical sandstone. The static modeling approach integrates seismic and well data to construct a structural model, allowing the spatial estimation of volume shale (), effective porosity (), water saturation (), and net to gross (NTG). Pre-stack seismic inversion is applied to generate detailed subsurface models, utilizing seismic data before the stacking process for more comprehensive information. By using data from various angles of incidence, this method improves resolution and enhances the ability to detect complex subsurface layers, producing a model with physical rock parameters like density and P-wave velocity. The study uses pre-stack seismic inversion to obtain an acoustic impedance profile, which is then applied in facies and petrophysical property simulation using geostatistical methods SGS and SIS to align simulation trends with inversion results. This integration is expected to produce a reliable model for hydrocarbon reserve volume calculation. Results indicate that the tight sandstone zones contain hydrocarbon reserves, primarily gas, due to the low porosity of the sandstone and the lower viscosity of gas compared to oil, enabling gas to move more easily into narrow pores. The simulated effective porosity, ranges from 0.01 to 0.18, volume shale from 0.01 to 1, water saturation from 0.64 to 1, and net to gross (NTG) values from 0.7 to 1.00, resulting in a GIIP volume of 4494 sm³. These findings demonstrate that integrating these methods effectively calculates hydrocarbon reserves in tight sandstone.